Does corticosteroid treatment affect the progression of pediatric IgA nephropathy – a systematic review and meta-analysis - Bebby Shelby; Cynthia Cynthia; Wida Ratna Sari; Erika Aini Putri; Yoga Eka Prayuda; Aditya Primadana; Andro Pramana Witarto (Pediatria Polska)
Immunoglobulin A nephropathy (IgAN) is an autoimmune disease in pediatric patients, with corticosteroid (CS) treatment remaining controversial. This meta-analysis evaluates the efficacy and safety of CS in pediatric IgAN patients. A systematic search of PubMed, ProQuest, and Wiley identified six studies with 208 patients. Outcomes included estimated glomerular filtration rate (eGFR), events of renal insufficiency, end-stage renal disease (ESRD), proteinuria, hematuria, IgA deposits, and side effects. Corticosteroid treatment showed a significant increase in eGFR (mean differences – MD: 11.84 [0.73–22.95] ml/min/1.73 m2), lower odds of having ESRD (odds ratios – OR: 0.21 [0.05–0.94]) and heavy proteinuria (OR: 0.15 [0.04–0.57]), and significant reduction in dipstick hematuria (MD: 2.89 [–3.85 to –1.93]). However, IgA deposits persisted despite CS treatment. Corticosteroid side effects were minimal. Corticosteroids may reduce glomerular damage and preserve renal function in pediatric IgAN patients, but limitations in addressing IgA deposits suggest the need for additional therapies.